2022
DOI: 10.1136/bmjopen-2022-063905
|View full text |Cite
|
Sign up to set email alerts
|

Asking youth and adults about child maltreatment: a review of government surveys

Abstract: ObjectivesIn this review we: (1) identify and describe nationally representative surveys with child maltreatment (CM) questions conducted by governments in low-income, middle-income and high-income countries and (2) describe procedures implemented to address respondents’ safety and minimise potential distress.DesignWe conducted a systematic search across eight databases from 1 January 2000 to 5 July 2021 to identify original studies with information about relevant surveys. Additional information about surveys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Exclusion criteria included (a) data that were not self-reported by a child or adolescent, (b) studies that reported data on child’s emotional or behavioral problems but not FV, (c) studies that focused on violence, bullying or abuse external to the family (e.g., school bullying or community violence), (d) articles in which the FV instrument was part of a population-level government survey or census that was not suitable for FV screening or assessment specifically (for a review of these types of surveys, see Campeau et al, 2022 ), (e) unpublished literature (e.g., dissertations) and (f) articles in a language other than English.…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria included (a) data that were not self-reported by a child or adolescent, (b) studies that reported data on child’s emotional or behavioral problems but not FV, (c) studies that focused on violence, bullying or abuse external to the family (e.g., school bullying or community violence), (d) articles in which the FV instrument was part of a population-level government survey or census that was not suitable for FV screening or assessment specifically (for a review of these types of surveys, see Campeau et al, 2022 ), (e) unpublished literature (e.g., dissertations) and (f) articles in a language other than English.…”
Section: Methodsmentioning
confidence: 99%